2018
DOI: 10.3390/polym10091004
|View full text |Cite
|
Sign up to set email alerts
|

A Pseudopeptide Polymer Micelle Used for Asymmetric Catalysis of the Aldol Reaction in Water

Abstract: Micelles assembled from amphiphilic molecules have proved to be ideal scaffolds to construct artificial catalysts mimicking enzymatic catalytic behavior. In this paper, we describe the synthesis of amphiphilic poly(2-oxazoline) derivatives with l-prolinamide units in the side chain and their application in asymmetric aldol reactions. Upon dissolution in water, the pseudopeptide polymers self-assembled into particles with different sizes, relying on the copolymer composition and distribution of hydrophilic/hydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…We found that the solvent had significant effect on this reaction, and the use of H 2 O as solvent, the reaction of trans ‐ β ‐nitrostyrene and propanal rendered the best results with high yield (80%) and enantioselectivity (95%) of corresponding adduct in the presence of 1 mol% micellar catalyst and 5 mol% benzoic acid (PhCOOH) additive at room temperature for 24 h (Table 1, Entry 5). This result might be ascribed to the good difussion of the micellar catalyst in water compared to other organic solvents 31 . In addition, the temperature was also a key factor.…”
Section: Resultsmentioning
confidence: 97%
“…We found that the solvent had significant effect on this reaction, and the use of H 2 O as solvent, the reaction of trans ‐ β ‐nitrostyrene and propanal rendered the best results with high yield (80%) and enantioselectivity (95%) of corresponding adduct in the presence of 1 mol% micellar catalyst and 5 mol% benzoic acid (PhCOOH) additive at room temperature for 24 h (Table 1, Entry 5). This result might be ascribed to the good difussion of the micellar catalyst in water compared to other organic solvents 31 . In addition, the temperature was also a key factor.…”
Section: Resultsmentioning
confidence: 97%
“…Nanoreactor is one of the most promising applications of polymeric micelles. 14,15 There are also reports on the use of polymeric micelles as nanocatalysts for organic reactions that can be done under mild conditions. 16 It holds many beneficial properties regarding structural variability, stability, functionality, and ability to carry out reactions under mild conditions.…”
Section: Introductionmentioning
confidence: 99%
“…These obstacles can be mitigated by using micellar systems such as surfactants or polymeric micelles , of which hydrophobic pockets can encapsulate and stabilize organic substrates in water and thus act as nanoreactors for organic synthesis. Nanoreactor is one of the most promising applications of polymeric micelles. , There are also reports on the use of polymeric micelles as nanocatalysts for organic reactions that can be done under mild conditions . It holds many beneficial properties regarding structural variability, stability, functionality, and ability to carry out reactions under mild conditions. For example, O’Reilly and co-workers installed 4-(dimethylamino)­pyridine (DMAP) moieties to the hydrophobic core of polymeric micelles that catalyzed acylation reactions in water .…”
Section: Introductionmentioning
confidence: 99%
“…26 In case of nanoreactors based on amphiphilic block copolymers a concise number of literature-known examples are available dealing with covalently bound organocatalysts. [27][28][29][30][31][32] A straightforward approach towards such systems is given by providing suitable ligand moieties for metal complexation directly attached to the polymer backbone. 19,[33][34][35][36][37][38][39] In this work we investigate the suitability of 3-chloro-2-hydroxypropyl methacrylate (ClHPMA) as platform to introduce ligand moieties within nanostructured soft matter.…”
Section: Introductionmentioning
confidence: 99%